PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM PUBLIK TERHADAP EMITEN YANG DIHAPUS PENCATATAN EFEKNYA DALAM RANGKA KETERBUKAAN INFORMASI (CONTOH KASUS: PT INOVISI INFRACOM TBK (INVS) TAHUN 2017) - Alfen Dwi Putra; Ariawan Gunandi (Fakultas Hukum Universitas Tarumanagara, 2021)
The capital market aims as a means of financing that brings together investors as parties who want to invest their funds or as parties who have more funds with issuers as parties who need funds to expand their business sector. Objects traded in the capital market are securities or commonly called securities. Legal protection for investors still has many weaknesses, so legal protection for investors creates uncertainty. Given the failure of the regulator to observe developments that occur or the lack of speed in adapting to rapid developments, it may result in the abandonment of the capital market in Indonesia by both foreign and domestic investors. To be able to achieve the goal of the capital market, namely to meet the funding needs of business actors, a legal protection mechanism is needed that can make potential investors feel safe investing in the capital market. Both the Capital Market Law, the Company Law, and the OJK Law have provided an opportunity for capital market players, especially investors, to save their assets when a delisting occurs.